A workshop to announce the 2011 Vietnam annual economic report - An, Nguyen Thi Thuc; Anh, Dau Kieu Ngọc (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 2, 2011)
Abstract. On May 17th, the University of Economics and Business - Vietnam National University, Hanoi (VNU) collaborated with the United Kingdom Department for International Development (DFID) and the Vietnam Center for Economic Research and Policy (VERP) to organize a workshop to announce the 2011 Vietnam Annual Economic Report titled “The Economy at a Crossroad.” The report is a major product of the strategic reseach program on “Macroeconomic Theory and Policy: the Condition of Economic Integration in Vietnam” hosted by the University of Economics and Business - VNU and conducted by the VERP. This annual report reviewed major economic issues in the past year, discussed economic perspectives for the coming year, and suggested policy recommendations.